Territorial planning of the plant cover in the Araucaria Domain: Assessment of the vegetation distribution in the Municipality of Erechim (Rio Grande do Sul, Brazil) - Oliveira-Costa, Jorge Luis; Graboski, Dulcimar (Aprender, 2025)
The objective of this communication is to assess the vegetation of Araucaria Domain in the municipality of Erechim (Rio Grande do Sul, Brazil). The methods adopted were developed according two phases: (i) the first referred to a bibliographic/cartographic review, (ii) and the second through field works and analyses relating to phytogeographic aspects. In Erechim, the potential vegetation conditions are difficult to define, not only due to the high rate of transformations, but also due to the high complexity in terms of the abiotic conditions. The current vegetation component of the study area shows, in terms of floristic, physiognomy and structure of the dominant communities, a strong disturbance, resulting from the effects of anthropic activities or the influence of periodic disturbances. Through this study, it was verified that the Araucaria Domain in the Erechim area is highly threatened by the growth of agroforestry activities, which historically occupy the region with extensive livestock farming and replace natural landscapes with large areas of wheat and soybean cultivation. The replacement of natural landscapes in artificial pastures seems to be the greatest obstacle to an ecologically sustainable land use policy for the Araucaria Domain in Erechim.
Keywords: Spatial analysis; Phytogeography; Araucaria domain; Erechim